Penyusunan Peta Indeks Resiko Banjir Dengan Teknologi Sistem Imformasi Geografis (SIG) Kecamatan Senapelan, Sukajadi Dan Lima Puluh - Yudha Andestian; Bambang Sujatmoko; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Flood is a disaster that can cause a lot of disadvantage to society, from materials or people`s life. Based on the survey from Royal Haskoning Team (2011), Senapelan district had 3 (three) spots of puddles. Sukajadi with 7 (seven) spots and Limapuluh district with 4 (four) puddles. The issue was came from the existed drainage system was still depends and relying on the natural channel, like brooks, swamps, and the others. Nevertheless, the brooks or swamps which flows to Siak River isn`t always good and that can potentially let some puddles and flood in several spots happens.The preparation of flood risk index map was based on insecurity index, vulnerability index and capacity index. The insecurity index parameter was based on the high , the duration and the frequency of the puddles. The vulnerability index parameter was based on the number of peoples, the dense of buildings, the male ratio and the ratio for under 15 (fifteen) peoples. The capacity index parameter was based on the existed flood pump condition, water tunnel, levee and drainage. Those parameters were analyzed by using Geographic Information System Technology (GIS)Based on the flood risk map for those three districts had 2 (two) sub-districts with index III, 6 (six) sub-districts with index II, and 9 (nine) sub-districts with index I. Based on the insecurity index, they were 3 (three) sub-districts with index IV, 4 (four) sub-districts with index III, 1 (one) sub-district with index II, and 9 (nine) sub-districts with index I. Based on the vulnerability index, they were 6 (six) sub-districts with index IV, 9 (nine) sub-districts with index III, 2 (two) sub-districts with index II. Based on the capacity index, they were 3 (three) sub-districts with index V, 14 (fourteen) sub-districts with index IVKeywords : SIG, flood risk map , insecurity, vulnerability, capacity.